Pleomorphic Adenoma of the Parotid Gland: A Report of Recurrence - Bulbulia, B. A.; Ahmed, M. R. (British Journal of Healthcare and Medical Research, 2022)
Pleomorphic adenomas (PA) are benign tumours of the salivary glands predominantly affecting the parotid gland. Presenting as a painless swelling they may be slow growing or fast growing and rarely metastasise. They can grow into extensive sizes if left untreated. Surgical excision is the treatment of choice without causing injury to the facial nerve (FN). Recurrences may occur as well as malignant transformation in a small percentage of cases.